Semantic Study of Taboo Words in Batak Culture - Santa Nananda Sebayang; Bernieke Anggita Ristia (Yayasan Bayt Shufiya Nusantara, 2025)
This study investigates the semantic change and socio-cultural functions of taboo words in Batak culture, focusing on how these expressions evolve and operate within traditional and modern interactions. Using a descriptive qualitative approach, data were collected through ethnographic interviews and participant observation involving native Batak speakers across different age and social groups. The analysis was conducted through data reduction, data display, and conclusion drawing techniques. Findings reveal that Batak taboo words have undergone various types of semantic change such as pejoration, narrowing, specialization, and metaphorical extension each reflecting deeply rooted cultural norms, customary values, and social hierarchies. These taboo expressions function not only as linguistic tools for emotional control and social regulation but also as symbolic carriers of identity and tradition. This study offers academic insight into the dynamic relationship between language and culture and highlights the importance of preserving indigenous semantic frameworks within endangered local languages.